Pituitary stalk interruption syndrome presenting in a euthyroid adult with short stature - Atif Nawaz, MBBS, FCPS-I, FRCR-I; Muhammad Azeemuddin, MBBS,MCPS,FCPS; Jehanzeb Shahid, MBBS,FCPS-I (Radiology Case Reports, 2018)
Pituitary stalk interruption syndrome (PSIS) is a distinct and rare clinical entity responsible for congenital hypopituitarism resulting in deficiency of pituitary hormones with deficiency of the growth hormone (100%) and gonadotropins (97.2%) being its most common presentation at the time of hospital encounter (Wang et al., 2015).Isolated sparing of thyroid-stimulating hormone (TSH) with deficiency of the remaining anterior pituitary hormones may be present in PSIS, as is true in our case. Therefore, it should be kept in mind at the time of examination in suspected cases of PSIS. Keywords: MRI